The Emergence of the First Dissident Organizations and the Dynamics of Ideological Development in Soviet Armenia in the Early 1960s - Harutyunyan, Shahen (History and Culture, 2025)
The internal political processes known as the "Khrushchevian thaw" and the Cold War’s steady intensification in the 1960s made it easier for dissident movements and ideas to emerge throughout the USSR’s republics. Under the totalitarian Soviet regime, dissident movements emerged and were organized by clandestine groups. Dissident groups emerged in Soviet Armenia throughout the 1960s and 1980s, primarily assuming control over the structure and direction of the dissident movement. This article’s goal is to examine and provide a thorough overview of the dissident groups that were established in Soviet Armenia in the early 1960s, as well as their operations. Researching and debating the dissidents that emerged in the USSR and the dynamics of their development—which influenced the emergence of dissident groups in Soviet Armenia—was the work assigned in order to achieve the aim. A historical and comparative approach was taken in doing the research. Interviews, archived materials, and governmental papers were all subjected to content analysis. It was suggested that the USSR’s second ideological battle began at the front of the dissent that emerged from both internal and exterior political events occurring in the Soviet Union. As dissident ideas gained traction in Soviet Armenia, a dissident struggle emerged. This fight grew more structured as dissident groups were established. The conclusion is that the dissident groups in Soviet Armenia, which emerged at the start of the 1960s, planned the continuous movements and were primarily responsible for planning and carrying out the conflict. The creation of the "National United Party" was crucial in fortifying Armenia’s vision of independence and completing the attitudes toward it that had prevailed up to that point.